Chaotic and nonchaotic behaviour in the mixmaster dynamics - Ferraz, K. [UNESP]; Francisco, G. [UNESP]; Matsas, G. E A [UNESP] (Elsevier, 1991)
We show that the mixmaster universe is nonchaotic with respect to the intrinsic time but chaotic with respect to the synchronous time. No appeal to any numerical simulation or other arguments are made, apart from the well known properties of the model. © 1991.